Lifetime Revictimization: Evidence From the Wisconsin Longitudinal Study - Kong, Jooyoung (Journal of interpersonal violence, 2024)
Despite the documented increasing prevalence of elder abuse victimization and its devastating health effects, a life-course view of the victimization experiences of older adults has rarely been adopted in the elder abuse literature. The current study investigated lifetime links between victimization experiences by examining the indirect effect of adverse childhood experiences (ACE) on elder abuse victimization via intimate partner violence (IPV) victimization in middle adulthood, and whether this indirect association would differ by gender. Using data from the Wisconsin Longitudinal Study, we analyzed the previous and current victimization experiences of a total of 5,391 older adults in their early 70s and estimated mediational and moderated mediation models. The key results indicated that a higher ACE score was associated with exposure to IPV victimization in middle adulthood, which was in turn associated with exposure to elder abuse victimization. This indirect association was stronger for women than for men. Regarding specific types of childhood victimization, parental physical abuse, sexual abuse, and witnessing domestic violence significantly predicted elder abuse victimization via IPV victimization. Our results support the phenomenon of lifetime victimization, whereby an individual experiences reoccurring forms of victimization across the life course from childhood to late adulthood. Findings highlight the compelling need for the assessment of cumulative victimization experiences and their impact on elder abuse victims. A life-course-based, trauma-informed approach would greatly enhance prevention and intervention services for elder abuse.